Modos de ensinar na diversidade cultural: fal(h)as reveladas em aulas dialógicas na educação de jovens e adultos - Oliveira, Deiseane Louise Santos (2013)
This paper aims to reflect on the methodological didactic procedures, from an analysis of the activities and materials used in a room of the Youth and Adult Education, which, in the intention of favoring dialogic classes, chose the theme of the work as structure of discussions seeking to meet even the principle of cultural diversity that presents itself as a brand that modality. To this end, the work is based on authors such as Freire (1979, 1982, 1985, 1993, 2007, 2008) Bakhtin (1992, 2006), Larrosa (2002, 2004, 2010, 2011), Hall (1992, 2006, 2009 ); Boaventura (2000, 2005). It is therefore an accurate reflection because convenes categories that reveal themselves involved in the teaching-learning Education for Youths and Adults (EJA), namely: dialogicity, study, subject, cultural diversity.